A proposed integrated mentoring practice framework to guide university supervisors during work - integrated learning - Du Plessis-De Beer, Annelize (University of Pretoria, 2024)
Dissertation (MEd (Curriculum and Instructional Design and Development))--University of Pretoria, 2023.